Socioeconomic disparities associated with mortality in patients hospitalized for COVID-19 in Colombia - Mendoza Cardozo, Oscar Ignacio; Pérez Bedoya, Juan Pablo; Ruiz Galvis, Lina Marcela; Pérez Aguirre, Carlos Andrés; Rodríguez Rey, Boris Anghelo; Barengo, Noël Christopher; Cardona Jiménez, Johnatan; Díaz Valencia, Paula Andrea (Frontiers in Public Health, 2023)
Socioeconomic disparities play an important role in the development of severe clinical outcomes including deaths from COVID-19. However, the current scientific evidence in regard the association between measures of poverty and COVID-19 mortality in hospitalized patients is scant. The objective of this study was to investigate whether there is an association between the Colombian Multidimensional Poverty Index (CMPI) and mortality from COVID-19 in hospitalized patients in Colombia from May 1 to August 15, 2021. This was an ecological study using individual data on hospitalized patients from the National Institute of Health of Colombia (INS), and municipal level data from the High-Cost Account and the National Administrative Department of Statistics. The main outcome variable was mortality due to COVID-19. The main exposure variable was the CMPI that ranges from 0-100% and was categorized into five levels: (i) level I (0% to 20%), (ii) level II (20% to 40%), (iii) level III (40% to 60%), (iv) level IV (60% to 80%); and (v) level V (80% to 100%). The higher the level, the higher the level of multidimensional poverty. A Bayesian multilevel logistic regression model was applied to estimate Odds Ratio (OR) and their corresponding 95% confidence intervals (CI). In addition, a subgroup analysis was performed according to the epidemiological COVID-19 waves using the same model. The odds for dying from COVID-19 was 1.46 (95% CI 1.4-1.53) for level II, 1.41 (95% CI 1.33-1.49) for level III and 1.70 (95% CI 1.54-1.89) for level IV hospitalized COVID-19 patients compared with the least poor patients (CMPI level I). In addition, age and male sex also increased mortality in COVID-19 hospitalized patients. Patients between 26-50 years-of-age had 4.17-fold increased odds (95% CI 4.07-4.3) of death compared with younger than 26-years-old patients. The corresponding for 51-75 years-old patients and those above the age of 75 years were 9.17 (95% CI 8.93-9.41) and 17.1 (95% CI 16.63-17.56), respectively. Finally, the odds of death from COVID-19 in hospitalized patients gradually decreased as the pandemic evolved. In conclusion, socioeconomic disparities were a major risk factor for mortality in patients hospitalized for COVID-19 in Colombia.